Targeting bacterial biofilm-related genes with nanoparticle-based strategies - Afrasiabi, Shima; Partoazar, Alireza (Frontiers in Microbiology, 2024)
Persistent infection caused by biofilm is an urgent in medicine that should be tackled by new alternative strategies. Low efficiency of classical treatments and antibiotic resistance are the main concerns of the persistent infection due to biofilm formation which increases the risk of morbidity and mortality. The gene expression patterns in biofilm cells differed from those in planktonic cells. One of the promising approaches against biofilms is nanoparticle (NP)-based therapy in which NPs with multiple mechanisms hinder the resistance of bacterial cells in planktonic or biofilm forms. For instance, NPs such as silver (Ag), zinc oxide (ZnO), titanium dioxide (TiO2), copper oxide (Cu), and iron oxide (Fe3O4) through the different strategies interfere with gene expression of bacteria associated with biofilm. The NPs can penetrate into the biofilm structure and affect the expression of efflux pump, quorum-sensing, and adhesion-related genes, which lead to inhibit the biofilm formation or development. Therefore, understanding and targeting of the genes and molecular basis of bacterial biofilm by NPs point to therapeutic targets that make possible control of biofilm infections. In parallel, the possible impact of NPs on the environment and their cytotoxicity should be avoided through controlled exposure and safety assessments. This study focuses on the biofilm-related genes that are potential targets for the inhibition of bacterial biofilms with highly effective NPs, especially metal or metal oxide NPs.